Enablers of sustainable industrial ecosystem: framework and future research directions. Issue 1 (14th January 2019) - Kumari, Sneha; Patil, Yogesh B.
Abstract : Purpose: The purpose of this paper is to dig out enablers of sustainable industrial ecosystem to develop a framework. Design/methodology/approach: To test the framework statistically, a structured questionnaire was designed. Measures for the questionnaire were adopted from an extensive literature review. Further, the questionnaire was pretested and further pilot study was conducted. Adding to this, the reliability and validity of the constructs was examined using confirmatory factor analysis followed by covariance-based structural equation modeling to test research hypotheses. Findings: The statistical analyses suggest that the model exceeds the threshold limit for goodness of fit after undergoing through few iterations. Normative pressure has a low effect than rest of the factors. Originality/value: The present study is a unique contribution in terms of its theoretical implications and practical use. Finally, research findings are concluded and further research directions is outlined.